Levels of Metals Harmful to Health in Various Types of Food - Góralczyk, Katarzyna; Dziubak, Anita; Kręźlewicz, Adrianna (Studia Ecologiae et Bioethicae, 2021)
Top-level human health depends on people’s eating habits. That is why, it is important to consume good quality food, both in terms of the presence of various contaminants, and the content of nutrients. Food contaminants, metals, and their compounds, are commonly found, since their presence in food, results from their common presence in various elements of the environment. The levels of micro-elements and macro-nutrients also testify to the health quality of food. Materials and methods: The materials for the study were food samples from organic and conventional production. The most popular fruit and vegetables in the diet in Poland, i.e., apples and carrots, were selected for research. The method of plasma excitation spectrometry (ICP-OES) was used to study the levels of metals harmful to health: cadmium (Cd), lead (Pb), arsenic (As), and mercury (Hg), as well as selected micro-elements and macro-nutrients: calcium (Ca), potassium (K), magnesium (Mg), phosphorus (P), iron (Fe), manganese (Mn), zinc (Zn), and aluminium (Al), in selected food products. Samples were mineralised by microwave techniques. Results: The content of harmful metals (Pb, Cd, Hg, As) in the tested apple and carrot samples were significantly lower than the maximum levels set in EU legislation, and did not differ, significantly, in conventional food vs. ecological. Similar results were also shown for micro-elements and macro-nutrients.